The effect of fear element on straddle hones jumpiness performance of girls - Mohameed, Sondos (Journal of Physical Education, 2008)
Sport activity bond to psychological situations ,I .e, fear and its effect on girls sport performance. The research Aims to study the importance of fear and its effect on the level of performance in straddle hones jumping performance .The research hypotheses that fear has a negative effect on the level of performance .The sample consisted of fourth and fifth year female students at the female teacher predatory institute at Selah-a-din province .It was concluded that is the absence of security and female assistant while jumping and the large number of students within one classroom .The research recommend the emphasis on theory and use of unless that affect outstanding motion performance